Neo-Ottoman Imaginaries in Contemporary Turkey
XVI, 321 p. 65 illus.
Keywords: This book presents gendered readings of cultural manifestations that relate to the Ottoman era as a preferred past and a model for the future. By means of claims of authenticity and the distribution of imaginaries of a homogenous desirable alternative to everyday concerns, as well as invoking an imperial past at the national level. In this mode of thinking, shaped around a polarised worldview, Republican ideals serve as a counter-image to the promoted splendour and harmony of the Ottomans. Yet, the stereotypical gender roles inextricably linked with this neo-Ottoman imaginary remain largely unacknowledged, dissimulated in the construction of the desire of an idealised past. Our adaption of a cultural studies perspective in this volume puts special emphasis on agency, gender, and authority. It provides a shared ground for the interrogation, through the contributions comprising this project of knowledge production about the past in light of what constitutes acceptable legitimacy in interpreting not only the canonical literature, but history at large. .